Anti-inflammatory effects of Agar free-Gelidium amansii (GA) extracts in high-fat diet-induced obese mice - Lee, Yunkyoung (Nutr Res Pract, 2018)
BACKGROUND/OBJECTIVES: Gelidium amansii (GA) contains plenty of agars and various biological substances, which make them a popular functional food to control body weight in previous studies. Unlike previous studies focused on agar in GA, objectives of this study were to investigate the effects of agar-free GA extract (AfGAE) on preventive and treatment models by using diets-induced obese (DIO) C57BL/6J mice. MATERIALS/METHODS: AfGAE were used to test their effects on the prevention (Exp-1) and treatment (Exp-2) against obesity after pilot study in DIO mice. The weight changes of the body and fat tissues and protein expression related to lipid metabolism and inflammation as well as plasma lipid profile and insulin were detected. RESULTS: Although AfGAE did not prevent long-term DIO, it did increase the levels of anti-inflammatory cytokine production and lipolysis protein. We further evaluated various doses of AfGAE in preventive and treatment models. As a result, our findings suggested that an AfGAE administration as a preventive model might be a better approach to achieve its anti-inflammatory and lipolysis-promoting effects in DIO mice. CONCLUSION: Although future studies to investigate the target materials such as polyphenols in AfGAE are required, the result suggests that GA without agar might be a therapeutic tool to improve health conditions related to inflammation.